2012
DOI: 10.4103/0973-1482.106531
|View full text |Cite
|
Sign up to set email alerts
|

The factors that have an impact on the development of brain metastasis in the patients with breast cancer

Abstract: As the prognostic and predictive factors showing the development of brain metastasis in breast cancer patients may be identified, follow-up also including the brain is important in order to take preventive measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
(50 reference statements)
0
4
1
Order By: Relevance
“…Therefore, the present study included the clinical conditions of patients in the development of the model; and multivariate analysis results revealed that meningeal metastasis was an independent factor for patient prognosis. There were 69 (16.8%) cases of meningeal metastases among the patients enrolled in the present study, which was slightly more than the numbers reported in previous studies ( 37 , 38 ). This may be associated with the extended survival of patients, as well as the wide application of magnetic resonance imaging in the diagnosis of brain tumors.…”
Section: Discussioncontrasting
confidence: 59%
“…Therefore, the present study included the clinical conditions of patients in the development of the model; and multivariate analysis results revealed that meningeal metastasis was an independent factor for patient prognosis. There were 69 (16.8%) cases of meningeal metastases among the patients enrolled in the present study, which was slightly more than the numbers reported in previous studies ( 37 , 38 ). This may be associated with the extended survival of patients, as well as the wide application of magnetic resonance imaging in the diagnosis of brain tumors.…”
Section: Discussioncontrasting
confidence: 59%
“…However, it is difficult for patients to survive longer than 7 months after diagnosis of BM [12]. Unlike other metastatic sites of cancers, BMs can make survival short due to decreased performance status of cancer patients [17]. These neurological sequelae make it hard to treat patients more comprehensively.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer (BC) is the second, after lung cancer (40–50%), most common cause of brain metastases (brain metastases from breast cancer – BMF-BC) (15–25%), and in this respect it comes before melanoma (5–15%) and renal and colorectal cancers [ 1 6 ]. At diagnosis of a BC of a locoregional extent, the risk of BMF-BC development is about 5% [ 4 , 7 9 ], but in patients with a generalized BC it reaches 7–17% [ 1 , 2 , 4 , 7 , 9 12 ], and in 1.3% of patients BMF-BC are the first symptom of a metastatic disease [ 7 , 9 ]. At autopsy, BMF-BC are found in about 30% of patients who died of BC, and in the group of patients with metastatic disease in 6 or more locations this percentage rises up to 86% [ 1 , 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…At diagnosis of a BC of a locoregional extent, the risk of BMF-BC development is about 5% [ 4 , 7 9 ], but in patients with a generalized BC it reaches 7–17% [ 1 , 2 , 4 , 7 , 9 12 ], and in 1.3% of patients BMF-BC are the first symptom of a metastatic disease [ 7 , 9 ]. At autopsy, BMF-BC are found in about 30% of patients who died of BC, and in the group of patients with metastatic disease in 6 or more locations this percentage rises up to 86% [ 1 , 2 , 4 ]. The incidence of BMF-BC is systematically increasing due to: increasing incidence of cancers related to population ageing, improved survival of BC patients associated with adjuvant treatment and better efficacy of systemic treatment of generalised BC, and also due to the progress in imaging technology (CT, MRI, PET) [ 1 , 3 , 5 , 10 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation